Sonde met die wese van die sondeleer - versteurde daad, verhouding of toestand? - F. B. Doubell (Acta Theologica)
This article focuses on the doctrine of sin. Many ethical questions and answers in religious or theological discussions are based on the view that someone has on the essence of sin. Ethical questions are always burning issues, while the essence of sin is a more theoretical and less favourite topic. The question addressed in this article is whether the essence of sin is found in our actions, our relationships or our condition as sinners. It is argued that our deranged actions and relationships are mere symptoms of our deranged condition. Just as cancer, death, trauma, sinful deeds and relationships, this condition did not change after Christ’s redemption. Christ’s redemption saved us from the power of sin, but the sinful condition, actions and relationship will only be rectified to the full with his second coming. Therefore, as all of us are still caught in this condition, we need to have more empathy for one another. We need to know that although we do not have someone else’s symptoms, we do have the same condition with only other symptoms.